Fibroblast-derived CXCL12 increases vascular permeability in a 3-D microfluidic model independent of extracellular matrix contractility - Holter, Jacob C.; Chang, Chia-Wen; Avendano, Alex; Garg, Ayush A.; Verma, Ajeet K.; Charan, Manish; Ahirwar, Dinesh K.; Ganju, Ramesh K.; Song, Jonathan W. (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer-associated fibroblasts (CAFs) play an active role in remodeling the local tumor stroma to support tumor initiation, growth, invasion, metastasis, and therapeutic resistance. The CAF-secreted chemokine, CXCL12, has been directly implicated in the tumorigenic progression of carcinomas, including breast cancer. Using a 3-D in vitro microfluidic-based microtissue model, we demonstrate that stromal CXCL12 secreted by CAFs has a potent effect on increasing the vascular permeability of local blood microvessel analogues through paracrine signaling. Moreover, genetic deletion of fibroblast-specific CXCL12 significantly reduced vessel permeability compared to CXCL12 secreting CAFs within the recapitulated tumor microenvironment (TME). We suspected that fibroblast-mediated extracellular matrix (ECM) remodeling and contraction indirectly accounted for this change in vessel permeability. To this end, we investigated the autocrine effects of CXCL12 on fibroblast contractility and determined that antagonistic blocking of CXCL12 did not have a substantial effect on ECM contraction. Our findings indicate that fibroblast-secreted CXCL12 has a significant role in promoting a leakier endothelium hospitable to angiogenesis and tumor cell intravasation; however, autocrine CXCL12 is not the primary upstream trigger of CAF contractility.